Strategy-performance linkage: methodological refinements and empirical analysis. Issue 3 (1st August 2016) - Anwar, Jamil; Hasnu, SAF
Abstract : Purpose: Strategic typologies are applied to investigate strategy–performance relationship. The typology of Miles and Snow (1978) is one of them, but the methodology applied for identification of strategic types for archival financial data is questionable on three grounds: no standard procedure for categorization of strategic types; identification of reactor strategy is always ignored; and the behavior of firms' strategic orientation over time is under-researched. Besides, the assumptions that viable strategies are expected to perform equally well, outperform reactors and distributed evenly are not overwhelmingly supported. The purpose of this paper is to address these issues. Design/methodology/approach: A refined scoring methodology is developed and used for identification of all strategic types, including reactors, by investigating the consistency of the firms over time. Empirical analysis using seven years of data of 121 joint stock firms of the textile sector in Pakistan is performed to test the assumptions regarding presence, distribution and performance of strategic types. Findings: There is significant difference in the distribution of the strategic types. Pure defenders and pure prospectors are non-existing, whereas a reasonable number of reactors are present. Overall difference in performance among strategies is generally insignificant and viable strategies outperformed reactors. The effect of size on performance is also insignificant. However, there is variation in performance of strategies with variation in size. Strategy is the better predictor of performance than size. Originality/value: The transition of strategic stance of the firms over time and the identification of reactor strategy from archived financial data are the important outcomes of the proposed methodology. The proposed methodology can be used for any longitudinal study for identification of all possible strategic types and can also be used for any other typological research.